2005
DOI: 10.1187/cbe.04-07-0047
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Biology Animations: Development and Impact on Student Learning

Abstract: Educators often struggle when teaching cellular and molecular processes because typically they have only two-dimensional tools to teach something that plays out in four dimensions. Learning research has demonstrated that visualizing processes in three dimensions aids learning, and animations are effective visualization tools for novice learners and aid with long-term memory retention. The World Wide Web Instructional Committee at North Dakota State University has used these research results as an inspiration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 24 publications
1
80
0
11
Order By: Relevance
“…As mentioned in the introduction, researchers suggested that dynamic computer animation can be used to give an accurate and rich picture of the dynamic nature of cellular processes, which are often very difficult to understand from text-based presentations of information . Similar findings in life sciences have also been reported by Stitch (2004), Mcclean et al (2005) and O'Day (2006). Stitch (2004) carried out a study in which, after a lecture on apoptosis, one group of 31 students who viewed an animation on apoptosis was compared to a group of 27 students who did not.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As mentioned in the introduction, researchers suggested that dynamic computer animation can be used to give an accurate and rich picture of the dynamic nature of cellular processes, which are often very difficult to understand from text-based presentations of information . Similar findings in life sciences have also been reported by Stitch (2004), Mcclean et al (2005) and O'Day (2006). Stitch (2004) carried out a study in which, after a lecture on apoptosis, one group of 31 students who viewed an animation on apoptosis was compared to a group of 27 students who did not.…”
Section: Discussionmentioning
confidence: 53%
“…While the students who saw the animation obtained significantly higher test scores than those who didn't, it can't be ruled out that the extra few minutes of exposure to the topic alone could explain, at least in part, the improved grade. McClean et al (2005) used animations for teaching protein synthesis to one group of students while another group of students were taught without animations. The group viewing the animations obtained significantly higher test scores than the group that didn't.…”
Section: Discussionmentioning
confidence: 99%
“…Four papers had no comparison or control group and did not measure a learning gain (Adamczyk, 2009;Blake, 2003;Dantas, 2008;McAteer, 1996); three evaluated an inappropriate student population (Dunsworth, 2007;McLean, 2005;Corton, 2006); eight had incomplete and/or irretrievable data (Fawver, 1990;Garg, 2002;Stith, 2004;McFarlin, 2008;Kohlmeier, 2003;Goldberg, 2000;Petersson, 2009 andGuy, 1992). Three other papers were also excluded on the basis of being a single-cohort study with no comparison to either a control group or as part of a before-and-after design (Dewhurst, 2000;McNulty, 2000;McNulty, 2004).…”
Section: Excluded Studiesmentioning
confidence: 99%
“…The students who viewed the animation scored significantly higher on the test than those who had not viewed the animation. McClean et al (2005) did a more comprehensive study in which small groups of students viewed a three-dimensional animation of protein synthesis in various combinations of individual study and a formal lecture versus individual study followed by a lecture without the animation. In all cases, the groups viewing the animation scored significantly higher in the follow-up test than the group that did not view it.…”
Section: Introductionmentioning
confidence: 99%